Análisis del dictamen constitucional sobre el error inexcusable en ecuador - Ronquillo-Riera, Orlando Iván; Cano-Paredes, Michael Alexander; Macías-Díaz, Adriana Doménica; Najera-Tello, Geovanna Michelle (IUSTITIA SOCIALIS, 2021)
Análisis del dictamen constitucional sobre el error inexcusable en ecuador